Indian Resilience and Rebuilding : Indigenous Nations in the Modern American West - Fixico, Donald Lee, 1951- (Book collections on Project MUSE., 2013)
This book's exploration of Native resilience in the twentieth century demonstrates how Native Americans reinvented themselves, rebuilt their nations, and ultimately became major forces in the United States. -- Adapted from publisher's description.